The Importance of Digitalization in Efforts to Increase MSME Income in Gending Village, Probolinggo Regency - Septiandika, Verto; Sucahyo, Imam; R, Andhi Nur; P, Renny Candra; Istiqomah, Riska Nur (Abdi Masyarakat, 2023)
Real Work Lecture (KKN) at Panca Marga University is a way of learning and working for students through various activities that are directly involved in society and trying to be part of society actively and creatively in the dynamics that occur in society in a short period of time. Students have an important role, namely as agents of change where in people's lives there is a change. So that with this KKN, students are able to solve problems that exist in society, one of which is in improving the community's economy. The rapid development of an increasingly sophisticated era in the modern era like today is very important for UMKM in developing their business. UMKM (Micro, Small and Medium Enterprises) in Indonesia is one of the fields that dominates business actors. The majority of business actors cannot develop and experience bankruptcy. However, UMKM have challenges in the business sector, namely digital marketing in order to be able to survive in competition. This is what makes UMKM change sales strategies through digital. With digitalization in the marketing strategy, it can help UMKM to be better than before.